Cardiovascular pharmacology II - Fowler, Raymond; MosbyJems (Firm) (St. Louis : MosbyJems, 2003)
'Focuses on the medications used to improve cardiac output and blood pressure, alkalinizing agents, and diuretics. The lecture focuses on the mechanism of action and indications and precautions for each medication as it pertains to ACLS. Medications discussed include norepinephrine, dopamine, dobutamine, vasopressin, calcium chloride, sodium nitroprusside, sodium bicarbonate, and furosemide.'--Container
Presenter, Raymond Fowler
VHS
Keywords: Cardiovascular Agents -- therapeutic use; Cardiovascular Diseases -- drug therapy